Comparing non-ipsative measures of party support - van der Eijk, Cees; Marsh, Michael (2011)
Non-ipsative measures of party preference (preference ratings for each of the parties of a political system) have become common in election studies. They exist in different forms, such as thermometer ratings or feeling scores, likes and dislikes scores, or choice propensities. Usually only one of these is included in a single survey, which makes it difficult to assess the relative merits of each. The Irish National Election Study 2002 (INES2002) contained three different batteries of non-ipsative party preferences, a feature which allows a systematic comparison between them. This paper investigates some properties of these different indicators. We focus mainly on the relationship between non-ipsative preferences and actual choices. This relationship is particularly revealing in a STV electoral system that allows voters to cast multiple ordered votes for candidates from different parties. Additionally, we investigate the latent structure of each of the batteries of party preferences and the relationships between them. We conclude that the three instruments are not interchangeable, that they measure different kinds of preferences. If the purpose is to study electoral choice and the process leading up to electoral choice, then the propensity to vote for a party is to be preferred over thermometer or feeling scores, and over likes/dislikes scores.